THE PORTRAYAL OF HEGEMONY IN THE MOVIE V FOR VENDETTA - Rafsel Khomeini (Jurnal Sarjana Ilmu Budaya, 2025)
This study examines the movie V for Vendetta through the lens of Gramsci’s theory of hegemony, focusing on political, cultural, and ideological forms. According to Gramsci, hegemony is maintained not only through coercion but also through consent, as ruling powers shape cultural norms, beliefs, and political structures to legitimize their dominance. In V for Vendetta, political hegemony is portrayed through authoritarian governance, constant surveillance, and propaganda, while cultural hegemony appears in the form of state-controlled media, historical revisionism, and the silencing of dissenting voices. Ideological hegemony is reinforced by instilling fear, obedience, and a distorted sense of justice, shaping how individuals perceive themselves and the world around them. This study uses a documentation method, which involves collecting, analyzing, and interpreting data from the film by repeatedly watching it and noting key scenes and dialogues that reflect Gramsci’s theory. Thirteen data points were identified and analyzed, revealing how hegemony operates and where it falters. The film ultimately suggests that although political, cultural, and ideological domination can sustain an oppressive regime, resistance remains possible through awareness, dissent, and collective action. By critically engaging with these portrayals, this study encourages readers to recognize and question hegemonic narratives in literature and society.